Tension Experience Induced By Nested Structures In Music - Sun, Lijun; Feng, Chen; Yang, Yufang (Frontiers in Human Neuroscience, 2020)
Tension experience is the basis for music emotion. In music discrete elements are always organized into complex nested structure to convey emotion, however, the processing of music tension in the nested structure remains unknown. The present study investigated the tension experience induced by the nested structure and the underlying neural mechanisms, using continuous tension rating task and electroencephalography (EEG) at the same time. Thirty musicians listened to music chorale sequences with non-nested, singly and doubly nested structures, and were required to rate their real-time tension experience. Behavioral data indicated that the tension experience induced by the nested structures had more fluctuations than the non-nested structure, and the difference mainly exhibited in the process of tension induction rather than tension resolution. However, the EEG data showed that larger LPCs was elicited by the ending chords in the nested structures compared with the non-nested structure, reflecting the difference in cognitive integration for long-distance structural dependence. The discrepancy between tension experience ratings and neural responses revealed the non-parallel relations between cognition and emotion. Furthermore, the LPC elicited by the doubly nested structure showed smaller scalp distribution than the singly nested condition, indicating a more difficult processing of the doubly nested structure. These findings revealed the dynamic tension experience induced by the nested structures and the influence of nested types, which shed new light on the raltionship between structure and tension in music.